Utilization of Plants as Traditional Medicine by the Community in Sumillan Village, Alla'District, Enrekang Regency - Hardianti Hardianti (Central Research Institute For Agriculture, 2023)
The purpose of this study was to find out what types of plants are used as traditional medicine in Sumillan Village, Alla' District, to find out how to process medicinal plants, and to find out which parts are used as medicinal plants in Sumillan Village, Alla' District. This research was carried out for approximately two months, from November to December 2020. Data collection techniques were carried out using in-depth interviews, field surveys and questionnaire techniques. The results of this study indicate that the types of medicinal plants used by the people in Sumillan Village were identified as many as 18 plant species used as traditional medicinal ingredients, the way the people in Sumillan Village processed these plants for treatment was boiling and then drinking, boiling then washing, pounding and then smearing, baked and then smeared, grated and then drunk, grated and then smeared, cut and then smeared, chewed and then drunk, crushed and then drunk, kneaded and pasted. However, the people in Sumillan Village more often use the concoction by boiling it and then drinking it to sick patients and the parts used are 5 parts of the plant that are used as ingredients for traditional medicine, namely leaves, stems, fruit, roots and sap.